2016
DOI: 10.14800/nc.844
|View full text |Cite
|
Sign up to set email alerts
|

An answer to "The Nagging Question of the Function of N-Acetylaspartylglutamate"

Abstract: In 1997, a paper was published entitled "The Nagging Question of the Function of N-Acetylaspartylglutamate". N-acetylaspartylglutamate (NAAG) is an unusual acetylated dipeptide that is synthesized by neurons, but whose complete metabolism requires four different enzymes and a specific receptor distributed among three different cell types in the brain. In 2007, it was hypothesized that the primary function of NAAG was that of a homeostatic neuronal-astrocyte-vascular system control mechanism. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, NAAG may account for some of the observed increase in tNAA, and could mark metabolic activity and availability for synthesis of glutamate (Rae, 2014). Baslow (2015) proposed a role of NAAG metabolism in complex task performance, so NAAG may increase as children engage in more cognitively demanding tasks (e.g., reading, math). This is especially relevant in the two regions investigated here, which are involved in executive functioning and language/reading processes that develop throughout childhood (Braver et al, 2021;Numssen et al, 2021;Richlan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAAG may account for some of the observed increase in tNAA, and could mark metabolic activity and availability for synthesis of glutamate (Rae, 2014). Baslow (2015) proposed a role of NAAG metabolism in complex task performance, so NAAG may increase as children engage in more cognitively demanding tasks (e.g., reading, math). This is especially relevant in the two regions investigated here, which are involved in executive functioning and language/reading processes that develop throughout childhood (Braver et al, 2021;Numssen et al, 2021;Richlan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, two papers were published, one that demonstrated for the first time that the enzyme that hydrolyzed NAA was only expressed in oligodendrocytes [4], and the other that showed that the enzyme that hydrolyzed NAAG was expressed "exclusively in astrocytic glial cells" [5]. The "nagging" question of the function of NAAG was considered in 1997 [6] and revisited in 2015 [7].…”
Section: Introductionmentioning
confidence: 99%